SDG 5 and Local Action Plan Challenges on Protection and Empowerment of Women and Children in Central Java’s Social Conflicts - Sabhita Kusuma Ayusia; Adi Setyorini Fitri; Ramadhanti Wita; Murniati Tri; Huda Marwan Nurul (E3S Web of Conferences)
The 2000 UN Security Council Resolution 1325 on Women, Peace, and Security was adopted in Indonesia through the National Action Plan for the Protection and Empowerment of Women and Children in Social Conflict (NAP P3AKS). At a local level, RAN P3AKS was adopted through Local Action Plan (LAP) P3AKS issued by six regions in Indonesia, namely Lampung, Aceh, Central Sulawesi, East Java, DIY, and Central Java. Central Java Province has issued LAP P3AKS through Central Java Governor Regulation Number 51c of 2023 concerning the Action Plan for the Protection and Empowerment of Women and Children in Social Conflict in Central Java 2023-2027. Through this research, the team intends to elaborate on the challenges in formulating and implementing the LAP to protect and empower women and children in Central Java. This research uses a qualitative research type with a case study approach. Data were collected through observation, in-depth interviews, and literature studies. This study's findings show several challenges in formulating and implementing LAP P3AKS in Central Java. Namely, there were differences in perception by local apparatus organisations, no disaggregated data on social conflicts, lack of budgeting and coordination of local government, and inactive participation.